Pengembangan LKPD Terhadap Model Pembelajaran PJBL Bagi Siswa SD - Suwartini, Sri; Ferryka, Putri Zudhah; Rahmawati, Isna; Rofisian, Nela; Irawati, Iisrohli (Universitas Muhammadiyah Magelang, 2024)
PJBL is a project-based learning to improve students' creativity by linking it to their daily lives. The focus of learning is on making a project to instill environmental awareness in Elementary Schools by producing a product in the form of a poster of me and my surroundings. In this learning, students are divided into groups of four to five children in one group. The pictures on the poster are the students' daily activities. Learning that is done in groups aims to increase students' self-confidence in expressing their opinions and respecting the opinions of other students. The purpose of this study was to determine the role of the PJBL-based learning model in increasing environmental awareness in Elementary Schools. This learning collaborated with grade V educators of Pancasila Education subjects to implement learning, and grade V students. This study used the Research and Development (R&D) method with the ADDIE model. Data collection techniques used observation and interviews to analyze the needs of educators and students. The data analysis technique used data collection, feasibility testing, reliability testing, and product moment correlation validity testing. The product feasibility test uses material experts, language experts, and module presentation experts. The results of this study produce a product in the form of a module that contains LKPD with a PJBL learning model. The product feasibility test states that this module product is suitable for use or does not need revision. The test results obtained quite good scores with scores above the learning objective achievement criteria (KKTP) set by educators. The results of the study and supported by previous research, that the PJBL learning model is effective in increasing environmental awareness in elementary schools.